MACHINE LEARNING FOR CYBERSECURITY: THREAT DETECTION AND PREVENTION - Sultana, Husna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The increasing sophistication and frequency of cyber threats pose significant challenges for organizations worldwide, necessitating advanced solutions for threat detection and prevention. Traditional cybersecurity measures, such as signature-based detection and rule-based systems, often fall short in identifying novel and complex attacks. This paper explores the application of machine learning (ML) as a transformative approach to enhance cybersecurity, focusing on its effectiveness in threat detection and prevention. Machine learning algorithms enable systems to learn from historical data, recognize patterns, and adapt to new threats in real-time. By leveraging techniques such as supervised, unsupervised, and reinforcement learning, ML enhances critical areas of cybersecurity, including intrusion detection systems (IDS), malware classification, phishing prevention, and behavioral analytics for user authentication. These advancements allow for automated threat detection, reducing response times and increasing the accuracy of identifying potential breaches. Despite its benefits, the integration of machine learning in cybersecurity is not without challenges. Issues related to data quality, the risk of adversarial attacks, and the interpretability of ML models pose significant hurdles. Furthermore, the balance between false positives and false negatives remains a critical concern for practitioners. This paper discusses various ML techniques used in cybersecurity, examines case studies demonstrating their application, and addresses the limitations and future directions of ML in this field. Ultimately, machine learning stands as a pivotal tool in the ongoing battle against cyber threats, offering the potential for more proactive and adaptive security measures. As the cyber landscape continues to evolve, the ongoing development of intelligent, data-driven solutions will be essential for effectively safeguarding organizations against emerging vulnerabilities and attacks.